Sobre uma classe de problemas elípticos com não linearidades do tipo côncavo-convexa - Pita, Maxwell de Sousa (2014)
In this work, we will establish a version of the Mountain Pass Theorem due to Martin Schechter [12], which will provide a Cerami sequence at a max-min level. As a consequence of this result, together with the Ekeland variational principle, we obtain some results of existence and multiplicity of solution for a class of semilinear elliptic problems involving a nonlinearity of concave-convex type